Fuzzy logic control of active suspension system equipped with a hydraulic actuator - Al-Ashtari, Waleed (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the Active Suspension System (ASS) of road vehicles was investigated. In addition to the conventional stiffness and damper, the proposed ASS includes a fuzzy controller, a hydraulic actuator, and an LVDT position sensor. Furthermore, this paper presents a nonlinear model describing the operation of the hydraulic actuator as a part of the suspension system. Additionally, the detailed steps of the fuzzy controller design for such a system are introduced.
Keywords: active suspension system; hydraulic actuator; nonlinear model; LVDT sensor and fuzzy controller